Heggie and Scheer's Moby-Dick : A Grand Opera for the Twenty-first Century - Wallace, Robert K., 1944- (Book collections on Project MUSE., 2013)
This book describes the world premiere of the American opera based on Melville's novel Moby-Dick. The author describes the creative process of writing the music and libretto, the rehearsals and stage design, and the opening night in Dallas in May 2010. -- ECIP Data View, Summary.